KESANTUNAN BERBAHASA DALAM DEBAT GUBERNUR DAN WAKIL GUBERNUR ACEH TAHUN 2024 (KAJIAN MAKSIM MENURUT GEOFFREY LEECH) - Zulkifli, Junaidi Junaidi; Eliana A Bakar, Eliana Eli; Darwis, Muhammad Darwis (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2025)
ABSTRACTPolitical debates played a crucial role in the 2024 Aceh Governor and Deputy Governor Election. The language used in these debates was heavily influenced by the nature of the discussions, especially in efforts to maintain a conducive and respectful atmosphere. Politeness served as a key element in fostering productive communication. This study focused on the application of Geoffrey Leech's maxims of politeness, aiming to analyze how these principles were reflected in the context of political debates. A qualitative approach was employed, utilizing a literature review method based on Leech’s politeness theory. The data were obtained from various sources related to the use of politeness in debate settings. The 2024 Aceh Governor and Deputy Governor debates show how effective communication can shape the public's perception of leadership. When candidates avoid unproductive verbal conflicts, the quality of the discussion improves significantly. Key principles like the maxims of respect and tact help create a more positive and focused debate atmosphere. They reduce the chance of personal attacks and keep the conversation centered on important issues. Using polite and thoughtful language not only enhances the candidates' public image, but also reflects their integrity and professionalism—qualities that are essential for ethical leadership.Keywords: Political Debate, Politeness, Politeness Maxim, Geoffrey Leech, Aceh Governor Election 2024.